The use of Stilbestrol and Synovex implants for steers on a wintering ration. - Koch, B.A.; Smith, E.F.; Cox, R.F.; Richardson, D.; Walker, G.L. (Kansas Agricultural Experiment Station, 2011)
This is the third test designed to study the value of stilbestrol implants for steer calves being fed a wintering-type ration. Synovex implants are being used for the second time. Both products are being used successfully to increase the daily gains of steers on high-energy fattening rations. Information concerning their value for calves being fed high-roughage wintering diets is rather limited, however.
Keywords: Beef; Stilbestrol; Synovex; Gain